Formulasi Sediaan Gel Hand Sanitizer dengan Kombinasi Ekstrak Lidah Buaya (Aloe vera L.) dan Ekstrak Daun Mengkudu (Morinda citrifolia L.): Formulation of Hand Sanitizer Gel with Combination of Aloe Vera (Aloe vera L.) Extract and Noni Leaves (Morinda citrifolia L.) Extract - Rezqi Handayani; Nurul Qamariah; Yelly Bestary (Jurnal Surya Medika (JSM), 2022)
Gel Hand Sanitizer is a hand sanitizer useful for cleaning or eliminating germs on hands. Aloe Vera (Aloe vera L.) contains active substances such as saponins that function as antiseptics. Substances contained in noni leaves (Morinda citrifolia L.) that act as antibacterials are anthraquinones. This study aims to determine whether the combination of Aloe vera extract (Aloe vera L.) and Noni leaf extract (Morinda citrifolia L.) can be formulated as a hand sanitizer gel. This study used experimental research methods; in this study, modifications were made to the formulas, namely F0, F1, F2, and F3, with modifications in the amount of carbopol and different glycerin. The tests on the four formulas, including organoleptic and pH tests, meet the requirements for testing preparations. At the same time, the homogeneity test showed that only the gel base was homogeneous, while formulas 1, 2, and 3 were not homogeneous. This research concludes that Aloe Vera (Aloe vera L.) extract and Noni leaf extract (Morinda citrifolia L.) cannot be formulated into hand sanitizer gel preparations because the texture of the preparations is not homogeneous and still leaves a color when applied on the hands.